MEMBANGUN SISTEM CODE STROKE PADA DUA RUMAH SAKIT PENDIDIKAN DI INDONESIA - Rakhmad Hidayat; Hirari Fattah Yasfi; Dinda Diafiri; Reyhan Eddy Yunus; Andi Ade Wijaya Ramlan; Taufik Mesiano; Mohammad Kurniawan; Al Rasyid; Salim Harris (PERDOSNI, 2020)
Code stroke system is rapid respond system for ischemic stroke patient’s care to have immediate therapy in order to increase effectiveness and achieve maximum outcome. Cipto Mangunkusumo Hospital and Universitas Indonesia Hospital are educational hospitals with different background, resources, facilities, and conditions in code stroke system implementation. This paper compares the code stroke system between both hospitals from some aspects, such as emergency unit health care providers, cost and facility, diagnostic imaging, initiator of code stroke system, observation room, availability of catherization lab, and communication within code stroke team. Code stroke system can be implemented in many hospitals correspondingly adjusting each of hospital conditions by maximizing advantages to cover the hospital’s shortcomings. Keywords: Code stroke, hospital, ischemic stroke, thrombectomy, thrombolysis